The Trends of Media and Communication Research among University Undergraduates in Sri Lanka - Raguram, S.; Wijeyananda, R. (The Forum of Asia-Pacific Academic Alliance for Communication and Journalism Associations, 2018)
The research culture among the undergraduates in Sri Lankan universities particularly in the field of media and communication research has been nourished and vastly concentrated by the academic communities since it’s become compulsory for the students as a dissertation project to partially fulfill the requirement for the completion of undergraduate degree programmes. Even though the research activity initiated as a part of the study, the stimulation and interest have been identified among the undergraduates to continue the analytical phenomenon in higher studies. This study is carried out in five selected universities which are situated in different parts of the country with the different ethnic composition: University of Jaffna from Northern Province, Trincomalee Campus of the Eastern University, University of Kelaniya, Sri Jayawardanapura University and Sri Palee Campus of University of Colombo from Western Province. The dissertations submitted by the final year undergraduates for the last three years from 2015 to 2017 are taken into consideration for the analysis. The study concludes that the research topics of undergraduates vastly move towards the recipient analysis from the content investigation in media and communication in recent days and much of the researches are mounted on find the impacts of electronic and new media compare to the less attention paid on print. While have look on methodologies of the dissertations, it’s noted that the larger number of undergraduates are chooses focus group discussions and sense making interviews with qualitative approach than traditional way of data collection such as questionnaires which mostly attended the quantitative research. Further, the study has found that the researches on unspoken issues according to the so-called cultural context in mainstream media such as finding the representation of homosexuality, promotion of domestic violence, reporting child abuses and ban and censorship are showcase as the new trends in research arena. Addition to this, the analysis revealed that the majority of the studies are geographically limited to the provinces, districts and sometimes the divisions where the undergraduates are residing or have the opportunities for their comfortable mobilization and the time frame also largely limited for few months. This paves the way to lack of competencies in researchers to generalize their findings at national level and bring them for the wider discussions in conferences and symposiums. The another barrier identified in take the outcomes of the undergraduates’ research attempts for extensive discussions that the dissertations done by the students in their mother tongue Sinhala or Tamil which also the medium of teaching – learning throughout their study programme in universities except one and only university from the Eastern Province which follows English as it’s medium of instruction.
Keywords: Undergraduates; Research Culture; Content Analysis; Recipient Investigation